A contribution to the optimization of wear behaviour of steel used for railway wheels - Werner Mombrei; Peter Ottlinger (Communications - Scientific letters of the University of Zilina, 2000)
In the next chapter the paper deals with the influences in the state of heat treatment of the wheel steel related both to the wear resistance and to the reason of the runout.